Effects of increasing pantothenic acid on growth performance and carcass characteristics of finish pigs reared in a commercial environment - C N Groesbeck; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2004)
A total of 1080 pigs (PIC), initially 89.0 ± 5.1 lb were used to determine the effects of increasing pantothenic acid on growth performance and carcass characteristics of growfinish pigs. Pigs were blocked by weight and gender, and were randomly allotted to treatment. Pigs were fed, in meal form, the experimental corn-soybean meal, added-fat diets in four phases. Dietary treatments consisted of a control diet (no added pantothenic acid), or the control diet with 22.5, 45.0, or 90.0 ppm added pantothenic acid from d-calcium pantothenate. Dietary treatments were fed from d 0 to 98 (89.0 to 272.5 lb). The first three dietary phases contained 5% choice white grease, and all diets contained 0.15% L-lysine HCl, trace mineral premix, and a standard vitamin premix manufactured with no pantothenic acid. Vitamins in the vitamin premix were supplemented at 300% of NRC guidelines. Added pantothenic acid had no effect on ADG, ADFI, or F/G, regardless of rate, and no significant differences were observed in carcass traits, including hot-carcass weight, dressing percentage, fat-free-lean index (FFLI), average backfat, and loin depth. In our experiment, added pantothenic acid did not influence growth performance or carcass composition of pigs reared in a commercial environment.; Swine Day, 2004, Kansas State University, Manhattan, KS, 2004
Keywords: Swine day; 2004; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 940; Kansas Agricultural Experiment Station contribution; no. 05-113-S; Swine; Pantothenic acid; Vitamin; Pigs